Study of osteoregenerative activity of periosteum of mandibular bones affected by cysts of different genesis - Mokryk, Олег; Lomnytsky, Ігор (Actual Problems of Medicine and Pharmacy, 2021)
In response to the prolonged increasing influence of the radicular cyst, there is an adaptive compensatory reaction of the adjacent bone tissue and periosteum located in the area of damage. However, in the available professional literature there is no data on the activity of the marker of osteoregeneration-alkaline phosphatase in the periosteum of the mandible, which is in the growth zone of osteoblastoclastoma. The purpose of the study: to study in a comparative aspect osteoregenerative activity of the periosteum of the mandibular bones affected by radicular cyst and cystic form of osteoblastoclastoma by using the histochemical method. Histochemical studies were performed in 10 patients with large radicular cysts (d>3.0 cm) located on the mandibles – 1st clinical group, and in 9 patients with cystic forms of osteoblastoclastomas, localized on the mandibles - 2nd clinical group. Determination of alkaline phosphatase in periosteal tissues of the mandible was performed by the method of simultaneous azo combination according to Kaplow. Prepared samples of histochemicals were studied under a light microscope, the received images were photographed. Digitized images of histochemicals were analyzed using the computer program ImageJ. The accumulation of alkaline phosphatase in the periosteum of the mandibular areas affected by osteoblastoclastomas is less intense compared to the process of synthesis of this enzyme in the periosteum of the mandible, which is affected by radicular cysts of large size. Osteoregenerative potential of periosteum of mandibular bones affected by radicular cysts is much greater than in the periosteum located in the growth zone of the cystic form of osteoblastoclastoma.